(untitled) (Ustozlar uchun, 2026)
This research thesis is devoted to the study of learning vocabulary at the early stage of language acquisition. Vocabulary plays a crucial role in developing basic language skills such as speaking, listening, reading, and writing. The study analyzes effective methods, techniques, and strategies for teaching vocabulary to beginner learners, focusing on age characteristics and cognitive abilities. Special attention is given to the use of visual aids, repetition, games, and contextual learning in the classroom. The research highlights the importance of motivation and interactive activities in enhancing vocabulary retention. The findings of the study can be useful for teachers and educators working with elementary-level learners.